Sleeve gastrectomy in a patient with situs inversus totalis: a case report - Almonla, Yaser M.; Abduljawad, Salim M.; Khazna, Miyad S.; Maghmoumeh, Rateb R. (International Surgery Journal, 2025)
The following is a case report of a 20-year-old female patient with morbid obesity and situs inversus totalis (SIT) who successfully underwent laparoscopic sleeve gastrectomy. Situs inversus (SIT) is a rare condition in which the organs are situated on the opposite side of their normal positions; it has some peculiarities during the surgery. Attention to detail in preparations before the surgery as well as modifications in the operating room allowed for the completion of the surgery in this case despite the numerous challenges. This report will show how the surgical plan was implemented in this clinical case, focusing on the intra-operative techniques and the post-operative course underscoring the flexibility of surgical treatment in such an anatomically complex case.